Spontaneous Twin Pregnancies Versus Twin Pregnancies Conceived with Assisted Reproductive Technologies - Sanlı Erkan; Pelin Öcal; İsmail Cepni; Barbaros Ilıkkan; Merve Barbaros; Rıza Madazlı (Medical Network, 2006)
OBJECTIVE: To ev aluate the differences between spontaneous and assisted reproductiv e technology (ART) conceived twin pregnancies in respects of gestational and neonatal outcomes. STUDY DESIGN: The comparison was made between 52 twin pregnancies conceived by ART and 80 spontaneous twins, deliv ered between y ears 2002 and 2004. Statistical analysis was perf ormed by the SPSS program, v ersion 11.5. RESULTS: Rates of nulliparity, preterm labor, incidence of caesarean section, hospitalization time and neonatal mortality were signif icantly higher in the ART group. ART itself was not a risk f actor for specif ic pregnancy complications such as pregnancy-induced hy pertension, gestational diabetes mellitus and premature rupture of membranes. Gestational age at deliv ery, the birth weights of both the first and second twins were comparable between the groups. CONCLUSION: ART conceiv ed twin pregnancies pose the neonate to higher risks of complication related to morbidity and mortality than spontaneous twin pregnancies. Maternal morbidity rate was equal in both groups.